Monitoring and assessment of reservoir siltation in arid environments using remote sensing: The Brézina Dam case study - Remmas, Zohra Hayat; Nouri, Tayeb; Benaradj, Abdelkrim (Brawijaya University, 2026)
The progressive silting up of dams in arid and semi-arid zones is a major problem, affecting storage capacity, the durability of hydraulic structures, and the sustainable management of water resources. In this context, the Brézina Dam, located in the El-Bayadh province (southwest Algeria) and with a capacity of approximately 123 million m³, was studied to characterize the morpho-sedimentary evolution of the catchment and reservoir over the period 2000–2025. The methodological approach is based on the spatio-temporal analysis of multi-date Digital Terrain Models (DTMs) using Google Earth Engine (GEE) and the calculation of the ?DTM, allowing for the identification and quantification of erosion and sedimentation zones. Descriptive and inferential statistical indicators, combined with automated thematic maps, were used to analyze topographic variations and estimate sediment volumes.The results highlight a dynamic dominated by sedimentation, with variations in the DEM (Digital Elevation Model) ranging from ?12 to +25 m and a statistically significant average increase in elevation (t ? 28.04; p < 10?¹?). Sedimentary deposits are mainly concentrated in valleys and near the dike, particularly in the 900–910 m elevation range observed in 2025. Volumetric analysis indicates that 59.54% of the surface area is affected by low-intensity sedimentation, compared to 31.42% affected by erosion, with an estimated eroded volume of 3.92 million m³ and a net positive sediment budget of +8.81 million m³.Beyond the hydraulic challenges, these results highlight the potential for valorizing dredged mud as organo-mineral amendments to improve the structure, water retention and fertility of sandy soils in arid areas, thus contributing to integrated and sustainable management of dams and agricultural systems. Keywords: Siltation, valorization, erosion, sedimentation, remote sensing, dam.